Pulveraven A from the fruiting bodies of Pulveroboletus ravenelii induces apoptosis in breast cancer cell via extrinsic apoptotic signaling pathway - Lee, D.; Yu, J.S.; Ryoo, R.; Kim, J.-C.; Jang, T.S.; Kang, K.S.; Kim, K.H. (Springer Nature, 2021)
Pulveroboletus ravenelii (Beck. et Curt.) Murr. (Boletaceae), commonly known as Ravenel’s bolete, is an edible and medicinal mushroom, and is also used for preparing mushroom-based dyes. As part of a continuing project to discover the bioactive natural products from wild mushrooms, we analyzed the methanol (MeOH) extract of P. ravenelii to identify metabolites with the anticancer activity. Chemical analysis of the MeOH extract combined with liquid chromatography？mass spectrometry (LC？MS) analysis led to the isolation of a phenolic compound, pulveraven A (PA), whose chemical structure was determined using a combination of 1D and 2D NMR and LC？MS analysis. In the present study, we investigated the cytotoxicity and anticancer mechanisms of pulveraven A using human breast cancer (MCF-7) cells, and demonstrated that it reduced cell viability of MCF-7 cells below 50% (71.74 ± 3.61 μM). Annexin V Alexa Fluor 488 binding assay and western blot results revealed that pulveraven A induced apoptotic cell death via the extrinsic apoptosis pathway, as indicated by the activation of initiator caspase-8 and executioner caspase-7. Furthermore, it was accompanied by an increase in the Bax/Bcl-2 ratio. These results suggest that pulveraven A induces apoptosis in breast cancer cells via the extrinsic apoptotic signaling pathway. ？ 2021, The Author(s), under exclusive licence to the Japan Antibiotics Research Association.